Catastrophic antiphospholipid syndrome and heparin-induced thrombocytopenia-related diseases or chance association?. Issue 2 (March 2015) - Tun, Nay T.; Krishnamurthy, Mahesh; Snyder, Richard
Abstract : Antiphospholipid syndrome (APS) and heparin-induced thrombocytopenia (HIT) are thrombotic disorders due to specific autoimmune-mediated antibodies. Catastrophic APS (CAPS), also known as Asherman's syndrome, is a life-threatening severe form of APS. Diagnostic criteria for CAPS include the development of a thrombotic event of three or more organs in less than a week with the presence of antiphospholipid antibodies and microvascular thrombosis on histology. Thrombocytopenia is seen in more than 60% of cases of CAPS. HIT is a life-threatening disorder with the clinical presentation of thrombocytopenia and arterial or venous thrombosis in patients who develop antibodies to heparin and platelet factor 4 typically within 10 days after starting heparin treatment. Due to the multiple similarities in clinical features and pathophysiology of CAPS and HIT, it has been postulated that these two antibody-mediated disorders may be related. We report two cases in which patients diagnosed with CAPS developed HIT very soon during the same admission as well as a case of a patient initially diagnosed with HIT who presented with CAPS years later.